Demografi Politik Kewargaan Daerah Pinggiran Kota Pangkalpinang - Rendy, Rendy; Wulansari, Dini; Zarina, Berlian (Jurusan Ilmu Politik Universitas Bangka Belitung, 2019)
Pangkalpinang continues to transform into a modern small town and certainly faces various dynamics of problems and complex challenges in citizenship. The complexity of urban citizenship has a diverse context, in accordance with the political demographics of suburban citizenship. This study compares the socio-political landscape and the dynamics of the challenges in the three research locations: Tuatunu, Kace Timur, and Beluluk, which are reflected in the daily political structure of citizenship. It uses qualitative approach based on observation, depth interview, and documentation. The findings reveal that the disparity of form and model of intervention in the changing context of the peripheral socio-political landscape causes the citizens being individualistic and capitalist and their spirit of communality increasingly eroded, there is a split community in Beluluk and Kace Timur in the context of the spirit of peripheral citizenship as the economic transit for citizens and the challenge of building a collective spirit of citizens. Furthermore, the social capital and political activity of citizens in the three villages shows a sharply difference in terms of resilience to various aspects of the local identity of each region such as the local cultural traditions or a shift of meaning and citizens' social capital.